Detailed studying of the spectrum of antimicrobial activity of several new condensed polynuclear arens - A. V. Gumenna; D. V. Rotar; S. Ye. Dejneka; N. D. Yakovychuk; О. О. Blinder (Zaporožskij Medicinskij Žurnal)
Uncontrolled use of antimicrobial drugs leads to the selection and spread of resistant strains of microorganisms. Рhosphonium compounds and their derivatives have been chosen as very perspective during searching of new highly active antimicrobial and antiseptic drugs.